ALASAN GURU TIDAK MENGGUNAKAN MEDIA BERBASIS TEKNOLOGI DI SMP DWIPAABADIKECAMATAN KATEMAN KABUPATEN INDRAGIRI HILIR PROVINSI RIAU - Rissa Mardika; Inoki Ulma Tiara; Waza Karia Akbar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning media is one of the tools used by teachers to facilitate the teaching and learning process in schools. However, there are still some teachers who have not or cannot use learning media optimally as a tool to facilitate the learning process. The purpose of this study is to describe